Spatial and trend analysis of gestational syphilis cases in Brazil from 2011 to 2020: an ecological study - Thales Philipe Rodrigues da Silva; Rafaela Siqueira Costa Schreck; Débora Caixeta Bernardes de Oliveira; Letícia Vieira Mascarenhas; Bianca Maria Oliveira Luvisaro; Bárbara Tideman Sartório Camargo; Eunice Francisca Martins; Giselle Lima de Freitas; Fernanda Penido Matozinhos (BMC, 2024)
Abstract Objectives To analyze the rate of gestational syphilis (GS) based on temporal trends over 11 years, as well as the spatial distribution of GS in Brazil, based on the identification of spatial clusters. Methodology An ecological, using Brazil and its regions as an analysis unit, based on gestational syphilis data reported in the Notifiable Diseases Information System (SINAN), from 2011 to 2020. Thematic maps were built for spatial data analysis, and the Prais-Winsten autoregressive model was used to verify the trend. Spatial analysis identified the distribution of clusters (high-high; low-low; high-low and low-high) of distribution of GS across Brazilian municipalities, using a 5% significance level. Results Gestational syphilis experienced a considerable increase in cases during the studied period, with a peak of 37,436 cases in 2018. The spatial distribution of the disease is heterogeneous in the country. A growing trend was observed in all states of Brazil, except for Espírito Santo, where it remained stationary, with a monthly variation of 10.32%. Conclusion The spatial and temporal trend analysis point to syphilis as an important public health problem. The numbers are alarming and show the urgent need for measures to prevent and control syphilis during pregnancy.